2014
DOI: 10.1186/1556-276x-9-695
|View full text |Cite
|
Sign up to set email alerts
|

Junctionless ferroelectric field effect transistors based on ultrathin silicon nanomembranes

Abstract: The paper reported the fabrication and operation of nonvolatile ferroelectric field effect transistors (FeFETs) with a top gate and top contact structure. Ultrathin Si nanomembranes without source and drain doping were used as the semiconducting layers whose electrical performance was modulated by the polarization of the ferroelectric poly(vinylidene fluoride trifluoroethylene) [P(VDF-TrFE)] thin layer. FeFET devices exhibit both typical output property and obvious bistable operation. The hysteretic transfer c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
1
0
0
Order By: Relevance
“…The peak intensity of the (104) face was found to gradually increase with the solvothermal treatment time, consistent with the evolution of the crystal orientation observed from the SAED patterns. This suggested that increasing the degree of crystallinity of hematite by increasing the solvothermal treatment time or temperature led to a preference for the (104) face, and this observation has also been reported elsewhere . The grain sizes estimated from the line broadening of the main diffraction peak (104) or (110) using the Scherrer equation were almost identical to the NP sizes estimated from TEM images.…”
Section: Resultssupporting
confidence: 82%
“…The peak intensity of the (104) face was found to gradually increase with the solvothermal treatment time, consistent with the evolution of the crystal orientation observed from the SAED patterns. This suggested that increasing the degree of crystallinity of hematite by increasing the solvothermal treatment time or temperature led to a preference for the (104) face, and this observation has also been reported elsewhere . The grain sizes estimated from the line broadening of the main diffraction peak (104) or (110) using the Scherrer equation were almost identical to the NP sizes estimated from TEM images.…”
Section: Resultssupporting
confidence: 82%